2011
DOI: 10.3389/fcimb.2011.00022
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis Tandem Repeat Proteins and Ank200 are Type 1 Secretion System Substrates Related to the Repeats-in-Toxin Exoprotein Family

Abstract: Ehrlichia chaffeensis has type 1 and 4 secretion systems (T1SS and T4SS), but the substrates have not been identified. Potential substrates include secreted tandem repeat protein (TRP) 47, TRP120, and TRP32, and the ankyrin repeat protein, Ank200, that are involved in molecular host–pathogen interactions including DNA binding and a network of protein–protein interactions with host targets associated with signaling, transcriptional regulation, vesicle trafficking, and apoptosis. In this study we report that E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 105 publications
(248 reference statements)
2
94
0
Order By: Relevance
“…We previously demonstrated that E. chaffeensis TRP120 strongly interacts with PCGF5, a component of the polycomb group (PcG) multiprotein PRC1-like complex, which maintains the transcriptionally repressive state of many genes, including hox genes (3,10). Coimmunoprecipitation of TRP120 with PCGF5 showed that TRP120 SUMOylation at Lys 432 regulates PCGF5 recruitment to the ehrlichial vacuole (11).…”
Section: Novel E Chaffeensis Ubiquitin Ligasementioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that E. chaffeensis TRP120 strongly interacts with PCGF5, a component of the polycomb group (PcG) multiprotein PRC1-like complex, which maintains the transcriptionally repressive state of many genes, including hox genes (3,10). Coimmunoprecipitation of TRP120 with PCGF5 showed that TRP120 SUMOylation at Lys 432 regulates PCGF5 recruitment to the ehrlichial vacuole (11).…”
Section: Novel E Chaffeensis Ubiquitin Ligasementioning
confidence: 99%
“…chaffeensis TRP120 is expressed by infectious dense-cored ehrlichiae in both arthropod and mammalian cells and is a major target of the human antibody response (8). TRP120 translocates across the vacuolar membrane through an unknown mechanism and localizes to different host subcellular compartments, including the nucleus (3,9). Notably, TRP120 is known to interact with several host cell proteins involved in posttranslational modification, including enzymes required for ligation and conjugation of ubiquitin (Ub) and ubiquitin-like modifiers (10).…”
mentioning
confidence: 99%
“…Ankyrin repeat-containing proteins (Anks) are important virulence factors of intracellular bacterial pathogens (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These effectors contain one or more ankyrin repeats, each of which consists of a 33-amino-acid motif that mediates proteinprotein interactions (15).…”
mentioning
confidence: 99%
“…Some of these intracellular pathogens deliver Anks into eukaryotic cells via a type IV secretion system (T4SS), with these "effectors" functionally mimicking or interfering with host cell processes to aid in the infection process (1,36,44,54). A recent report has identified the role of T1SS for extracellular secretion of E. chaffeensis Ank200, also suggesting that the T1SS is functional across Rickettsiales (59).…”
mentioning
confidence: 99%